Artificial intelligence adaptive control to improve on real-time dynamic process performance : ball burnishing machining operation as its basis - Lye, Sun Woh (2008)
In this project , a generic intelligent feedback system (GIFS), an alternative adaptive control approach, has been developed to monitor and minimise the undersirable variations in the machining process variables. Ball burnishing, a post-machining finishing process, is used as the basis for investigation.